Towards mm-wave spectroscopy for dielectric characterization of breast surgical margins. (June 2019) - Summers, Paul E.; Vingiani, Andrea; Di Pietro, Salvatore; Martellosio, Andrea; Espin-Lopez, Pedro F.; Di Meo, Simona; Pasian, Marco; Ghitti, Michele; Mangiacotti, Marco; Sacchi, Roberto; Veronesi, Paolo; Bozzi, Maurizio; et al.
Abstract: Purpose: The evaluation of the surgical margin in breast conservative surgery is a matter of general interest as such treatments are subject to the critical issue of margin status as positive surgical margins can undermine the effectiveness of the procedure. The relatively unexplored ability of millimeter-wave (mm-wave) spectroscopy to provide insight into the dielectric properties of breast tissues was investigated as a precursor to their possible use in assessment of surgical margins. Methods: We assessed the ability of a mm-wave system with a roughly hemispherical sensitive volume of ∼3 mm radius to distinguish malignant breast lesions in prospectively and consecutively collected tumoral and non-tumoral ex-vivo breast tissue samples from 91 patients. We characterized the dielectric properties of 346 sites in these samples, encompassing malignant, fibrocystic disease and normal breast tissues. An expert pathologist subsequently evaluated all measurement sites. Results: At multivariate analysis, mm-wave dielectric properties were significantly correlated to histologic diagnosis and fat content. Further, using 5-fold cross-validation in a Bayesian logistic mixed model that considered the patient as a random effect, the mm-wave dielectric properties of neoplastic tissues were significantly different from normal breast tissues, but not from fibrocystic tissue. Conclusion: Reliable discrimination of malignant from normal, fat-rich breast tissue to a depth compatible with surgical margin assessment requirements was achieved with mm-wave spectroscopy. Highlights: Mm-wave dielectric properties of breast cancer differed from normal tissues. Benign lesions had mm-wave dielectric properties of intermediate to normal and malignant tissues. Mm-wave spectroscopy may have a role in surgical margin management. Future studies should account for inter-individual differences in breast dielectric properties.